2021
DOI: 10.3390/jof7090750
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of a Rare Fungal PKS CgPKS11 Promotes Chaetoglobosin A Biosynthesis, Yet Defers the Growth and Development of Chaetomium globosum

Abstract: We previously reported that chaetoglobosin A (ChA) exhibits a great potential in the biocontrol of nematodes and pathogenic fungi. To improve the production of ChA, a CRISPR-Cas9 system was created and applied for eliminating potential competitive polyketide products. One of the polyketide synthase encoding genes, Cgpks11, which is putatively involved in the biosynthesis of chaetoglocin A, was disrupted. Cgpks11 deletion led to the overexpression of the CgcheA gene cluster, which is responsible for ChA biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In this study, the Δpks1-TE-C500 strain also shows defects in growth and the development of conidia demonstrated by smaller-sized, less, and delayed germination. Our results are similar to the reports found in other fungi after deletion of PKS [ 30 , 33 35 ]. Given the fact that pks1 expression significantly decreased in the Δpks1-TE-C500 strain, all these findings indicate that TE on pks1 act as a trigger for growth and sporulation in F .…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the Δpks1-TE-C500 strain also shows defects in growth and the development of conidia demonstrated by smaller-sized, less, and delayed germination. Our results are similar to the reports found in other fungi after deletion of PKS [ 30 , 33 35 ]. Given the fact that pks1 expression significantly decreased in the Δpks1-TE-C500 strain, all these findings indicate that TE on pks1 act as a trigger for growth and sporulation in F .…”
Section: Discussionsupporting
confidence: 93%
“…Blastp analysis revealed that CgTF1 had 77.19, 38.10, 30.56, 26.10 and 24.64% identity to a GAL4-like Zn 2 Cys 6 binuclear cluster DNA-binding domain protein ( C. globosum E-C-2, QHD43140.1), CheC ( P. expansum , CAO91859.1), CheF ( P. expansum , CAO91864.1), GAL4 ( Aspergillus sclerotialis , RJE27110.1) and Gal4p ( S. cerevisiae , NP_015076.1), respectively. To characterize the functional roles of CgTF1 on ChA biosynthesis, CgTF1 was deleted using an established “suicide” CRISPR-Cas9 system (Xiang et al, 2021 ). All gene-targeted plasmids were constructed based on plasmid pCRISPR-Hyg ( Supplementary Figure 1 ), which contain the Cas9 and gDNA expression cassettes and a hygromycin B resistance marker.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we successfully established a “suicide” CRISPR-Cas9 system to promote gene deletion in C. globosum NK102 (Wang Y. et al, 2016 ; Xiang et al, 2021 ). Plasmids for Cgtf1 or Cgtf6 deletion were constructed based on plasmid pCRISPR-Hyg ( Supplementary Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…This approach has been adapted for BGC engineering in Chaetomium globosum. 79 2.4.3 Episomal CRISPR/Cas systems. Another popular delivery approach is to encode CRISPR/Cas components on episomal vectors housing an AMA1 fungal autonomous replication element (Fig.…”
Section: Reviewmentioning
confidence: 99%